Autism Spectrum Disorder (ASD) - from the viewpoint of an Icelandic employer - Ellen Ósk Valtýsdóttir 2001-; Fanndís María Sverrisdóttir 2001- (2023)
Autism Spectrum Disorder (ASD) is characterized by different social interactions and behavior patterns. This study looked at attitudes towards ASD and employment. There are many individuals with ASD who are unemployed worldwide, thus it is important to try to understand why that is. The participants were 11 companies in Iceland. The participants were sent a questionnaire to assess their attitudes. No participant stated that they would not hire someone with ASD. Out of the 11 companies only four had an employee with ASD. The results showed that there was a significant difference between larger and smaller businesses, with the larger companies agreeing that hiring persons with disabilities would be more expensive. The results also showed that there was a significant difference between companies who had ASD employees and those who did not, that is companies who did not have ASD employees said that it was less expensive to employ ASD. In conclusion, this topic is important because unemployment is a big issue for people with ASD and needs to be explored further. Keywords: ASD, employers, attitudes, companies Einhverfurófsröskun einkennist af óhefðbundnum félagslegum samskiptum og hegðunarmynstrum. Þessi rannsókn skoðaði muninn á viðhorfum atvinnuveitendum fyrirtækja með fleiri en 50 og færri en 50 starfsmenn og hvort fyrirtæki höfðu einhverfan starfsmann innan fyritækisins, gagnvart einhverfurófsröskun (ASD). Margir með einhverfu eru atvinnulausir og þarf því að skoða þetta vandamál betur. Þátttakendur voru atvinnuveitendur í 11 fyrirtækjum á Íslandi (N = 11). Þátttakendum var sendur spurningalisti til að kanna viðhorf þeirra. Enginn þátttakandi sagði að þeir myndu ekki ráða inn einstakling með einhverfu. Af þessum 11 fyrirtækjum voru fjögur sem höfðu starfsmann með einhverfu Niðurstöður sýndu marktækar niðurstöður á breytu, þar sem stærri fyrirtæki voru meira sammála staðhæfingunni um að það kosti meira að ráða inn einstakling með einhverfu. Einnig sýndu niðurstöður marktækan mun á fyrirtækjum eftir því hvort það ...